2019
DOI: 10.1186/s13098-019-0455-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum visfatin levels and atherosclerotic plaque in patients with type 2 diabetes

Abstract: Background Visfatin is a multifaceted protein that plays an important role in regulating a variety of physiological and pathological processes, including obesity, diabetes and cardiovascular disease. However, circulating visfatin levels in atherosclerosis plaque progression in patients with type 2 diabetes, or its association with the vascular territory affected remain unclear. Methods We evaluated the relationship between visfatin levels and carotid or femoral artery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
1
30
0
4
Order By: Relevance
“…Visfatin, also known as nicotinamide phosphoribosyl-transferase (Nampt), is an adipocytokine secreted by adipocytes, macrophages, and inflamed endothelial tissue. High levels of visfatin are observed in patients with obesity, type 2 diabetes mellitus, chronic inflammatory conditions and cancer, and an association between serum visfatin levels and cardiovascular disease has recently been observed in patients with type 2 diabetes [ 123 , 124 , 125 ]. Moreover, BAT exhibits multiple cytoplasmic lipid inclusions and numerous mitochondria.…”
Section: Functional Variation Of Adipocytesmentioning
confidence: 99%
“…Visfatin, also known as nicotinamide phosphoribosyl-transferase (Nampt), is an adipocytokine secreted by adipocytes, macrophages, and inflamed endothelial tissue. High levels of visfatin are observed in patients with obesity, type 2 diabetes mellitus, chronic inflammatory conditions and cancer, and an association between serum visfatin levels and cardiovascular disease has recently been observed in patients with type 2 diabetes [ 123 , 124 , 125 ]. Moreover, BAT exhibits multiple cytoplasmic lipid inclusions and numerous mitochondria.…”
Section: Functional Variation Of Adipocytesmentioning
confidence: 99%
“…Zheng и соавт. [26] показали, что уровни в крови висфатина у пациентов с СД и с АСБ в сонной артерии были выше, чем у пациентов с СД без АСБ. Результаты логистического регрессионного анализа показали, что более высокий уровень висфатина в крови был независимым предиктором наличия АСБ.…”
Section: Discussionunclassified
“…Pearson's correlation analyses suggested that the serum levels of visfatin positively correlated with waist circumference, waist hip index, TGs, and the number of plaques. Logistic regression analysis revealed that a higher level of visfatin in serum is an independent predictor of the presence of atherosclerotic plaques [97].…”
Section: Visfatinmentioning
confidence: 99%